Overuse Injuries in Children: A Homoeopathic Approach - Raghul.G, Dr Ravi; Shivaprasad, Dr Jyoshna (Indian Journal of Integrative Medicine, 2024)
The increasing participation of children in organized competitive sports has led to a rise in overuse injuries, posing risks of limb deformity and impairment. This article explores the diagnostic, prognostic, and therapeutic applications of HOMOEOPATHY in addressing overuse injuries in children. Overuse injuries result from repetitive strain on musculoskeletal structures, particularly prevalent during periods of physical growth and immaturity. Common injuries include stress fractures, traction apophysitis, and chronic physeal damage. In the Indian context, lack of awareness and inappropriate self-treatment exacerbate these injuries. Recognition of warning signs, such as persistent soreness, is crucial for early intervention. Rehabilitative approaches involve rest, gradual strengthening, and attention to flexibility. HOMOEOPATHY offers personalized remedies targeting specific musculoskeletal entities, aiding in recovery and preventing recurrence. Remedies such as Rhus Toxicodendron, Ruta, and Bryonia address tendon and joint issues, while Arnica montana and Symphytum officinale target trauma-related injuries. Individualized homeopathic treatment, alongside appropriate rehabilitation regimens, facilitates faster recovery from overuse injuries in children.